X-ray radiation during pulsed laser treatment of opal matrices - A. F. Belyanin; V. V. Borisov; V. V. Popov (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The paper presents the structure and preparation conditions of opal matrices (ordered 3D-lattice packing of X-ray amorphous SiO2 spheres with a diameter of ≈250 nm), as well as experimental data on nonlinear optical effects in opal matrices with pulsed laser excitation at wavelengths: 1040 nm, 510 nm in conjunction with 578 nm, and 366 nm. The authors investigate the energy spectra of X-ray radiation induced in the samples by laser irradiation.